(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2023)
The rise and consolidation of neoliberalism witnessed, inter alia, the emergence of a discourse on the causes of poverty centred on public corruption, which has informed the mainstream of development. In this perspective, the goal of “long-term economic growth and shared prosperity” has to be achieved – parallel to the implementation of core economic reforms – by combating corruption. As a matter of fact, governments of developing countries are called upon to fight corruption, under the watchful eye of a civil society, which is presumed not to question the framework of neoliberal reforms. Here, we would like to propose a critical reading of this normative framework by questioning, in a historical perspective, the main theoretical assumptions underlying it as well as the notion of corruption, which informs it. Not least, we will raise the question of which spaces, if any, are left to take into consideration the role to be played by redistributive public policies in the struggle against poverty in the world’s South. Finally, we will propose some reflections resulting from a long period of fieldwork research in the Indian state of Odisha, historically plagued by severe levels of material poverty and social inequality, and affected by the proliferation of corruption practices inherent to the exploitation of its abundant natural resources.